2013
DOI: 10.3390/antibiotics2010028
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Multi-Drug Resistance (MDR) Efflux Pump Inhibitors of Gram-Positive Bacteria S. aureus

Abstract: The paper focuses on recent achievements in the search for new chemical compounds able to inhibit multidrug resistance (MDR) mechanisms in Gram-positive pathogens. An analysis of the results of the search for new efflux pump inhibitors (EPIs) for Gram-positive bacteria, which have been performed over the last decade, indicates that almost all efforts are focused on the NorA (MFS) efflux pump in S. aureus. Considering the chemical structures of the NorA EPIs that have been identified, it can be observed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
113
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 71 publications
4
113
0
9
Order By: Relevance
“…Bacteria use efflux pumps as a self-defense mechanism to remove antibiotics from the cell. The activity through efflux pumps results in sub-lethal drug concentrations at the active site that often predisposes the organism to the development of high-level resistance against antimicrobial agents [26]. Several studies have reported the crucial role of phytochemistry in the search for effective efflux pumps inhibitors (EPIs), especially against Gram-positive bacteria such as S. aureus and S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria use efflux pumps as a self-defense mechanism to remove antibiotics from the cell. The activity through efflux pumps results in sub-lethal drug concentrations at the active site that often predisposes the organism to the development of high-level resistance against antimicrobial agents [26]. Several studies have reported the crucial role of phytochemistry in the search for effective efflux pumps inhibitors (EPIs), especially against Gram-positive bacteria such as S. aureus and S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
“…The other possible mechanism by which these natural agents might be exerting their antimicrobial effect or synergistic effect with antibiotics is through inhibition of bacterial efflux pumps [26]. Bacteria use efflux pumps as a self-defense mechanism to remove antibiotics from the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that increased resistance to antibiotics, biocides and dyes has been associated with NorA and NorB mediated efflux pumps (Handzlik et al, 2013;Sabatini et al, 2012;Truong-Bolduc et al, 2005;Ding et al, 2008). However, antimicrobial resistance associated with NorA and NorB efflux pumps is poorly characterized in S. aureus (Handzlik et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, antimicrobial resistance associated with NorA and NorB efflux pumps is poorly characterized in S. aureus (Handzlik et al, 2013). NorA uses proton motive force to energize the transport of antimicrobial compounds across the cell membrane (Neyfakh et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation